2021
DOI: 10.1038/s41598-021-99568-3
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial signaling peptide MOTS-c improves myocardial performance during exercise training in rats

Abstract: Cardiac remodeling is a physiological adaptation to aerobic exercise and which is characterized by increases in ventricular volume and the number of cardiomyocytes. The mitochondrial derived peptide MOTS-c functions as an important regulator in physical capacity and performance. Exercise elevates levels of endogenous MOTS-c in circulation and in myocardium, while MOTS-c can significantly enhance exercise capacity. However, the effects of aerobic exercise combined with MOTS-c on cardiac structure and function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…NRG1-ErbB4-C/EBPβ signaling is a key pathway implicated in regulating the adaptation in cardiomyocytes induced by exercise ( 46 , 47 ). Our previous findings suggested that both MOTS-c and aerobic exercise improved myocardial performance in rats ( 48 ). Based on the results of function enrichment analysis of DEGs and the exercise-like effects of MOTS-c in myocardium, we determined the mRNA and protein expression of NRG1 and ErbB4 to explore the molecular mechanisms of MOTS-c induced beneficial effects in cardiac.…”
Section: Resultsmentioning
confidence: 92%
“…NRG1-ErbB4-C/EBPβ signaling is a key pathway implicated in regulating the adaptation in cardiomyocytes induced by exercise ( 46 , 47 ). Our previous findings suggested that both MOTS-c and aerobic exercise improved myocardial performance in rats ( 48 ). Based on the results of function enrichment analysis of DEGs and the exercise-like effects of MOTS-c in myocardium, we determined the mRNA and protein expression of NRG1 and ErbB4 to explore the molecular mechanisms of MOTS-c induced beneficial effects in cardiac.…”
Section: Resultsmentioning
confidence: 92%
“…MOTS‐c is a mitochondrial‐encoded peptide that improves age‐related skeletal muscle insulin resistance and enhances adaptation to metabolic stress (Kim et al, 2018 , 2019 ; Reynolds et al, 2021 ). Its potential as an important regulator of systemic metabolism was highlighted in a series of studies examining changes in circulating MOTS‐c following high‐intensity exercise (Reynolds et al, 2021 ; von Walden et al, 2021 ) and by exogenously providing MOTS‐c in rodent models (Reynolds et al, 2021 ; Yuan et al, 2021 ). The goal of this study was to better understand the relationship between MOTS‐c and exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial open reading frame (ORF) of the 12S rRNA type‐c (MOTS‐c) has emerged as a strong candidate for influencing intracellular communication and whole‐body physiology (Kim et al, 2017 ; Kim et al, 2018 ; Lee et al, 2016 ; Li & Laher, 2015 , Lu, Tang, et al, 2019 ; Reynolds et al, 2021 ; Yuan et al, 2021 ). MOTS‐c is abundantly expressed in skeletal muscle (D'Souza et al, 2020 ; Lee et al, 2015 ) and functions, in part, to increase glucose metabolism by enhancing insulin sensitivity, energy expenditure, and heat production (Lee et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Activating AMPK, increasing the phosphorylation level of eNOS, and decreasing the expression of the apoptotic factor Bax can help reduce the myocardial infarction area, enhance cardiac function, improve the survival rate of myocardial cells, and play a cardiac protective role in a dose-dependent manner (HNG,2 mg/kg is the best) in the MI-R mouse model. Yuan et al (61) investigated the effects of MOTS-c on cardiac function and structure of rats during chronic aerobic exercise by intraperitoneal injection of MOTS-C, and detected echocardiography by HEMO dynamics with HE staining. After analyzing cardiac function, it was found that MOTS-c could improve cardiac mechanical efficiency, enhance cardiac systolic function, and have a tendency to improve diastolic function, thus improving cardiac function.…”
Section: Mitochondrial-derived Peptides and Myocardial Infarctionmentioning
confidence: 99%
“…Yuan et al. ( 61 ) investigated the effects of MOTS-c on cardiac function and structure of rats during chronic aerobic exercise by intraperitoneal injection of MOTS-C, and detected echocardiography by HEMO dynamics with HE staining. After analyzing cardiac function, it was found that MOTS-c could improve cardiac mechanical efficiency, enhance cardiac systolic function, and have a tendency to improve diastolic function, thus improving cardiac function.…”
Section: Mitochondrial-derived Peptides and Diseasementioning
confidence: 99%